Women, crime and punishment in Ireland: life in the nineteenth-century convict prison - Farrell, Elaine (Cambridge University Press, 2020)
"This book describes the history of the Irish female convict prison's history, structure and space, the historiography of Irish punishment and imprisonment, and the sources and methods. It outlines how the Irish Convict System developed in the wake of the end of transportation. It explores the aims and motivations of the Convict Directors who headed the System, and demonstrates how the approach won immediate praise and had widespread international influence. Optimism that the Irish Convict System had solved recidivism, however, was not to last and in the 1870s the establishment of the General Prisons Board initiated further changes. This book also explores the establishment of a singularly female prison managed mostly by female staff. It demonstrates, using quantitative and qualitative evidence, that a stay in Ireland's female convict prison was statistically unusual, even though the women housed therein were in other respects 'ordinary' women"--